2022
DOI: 10.1007/s00442-022-05105-y
|View full text |Cite
|
Sign up to set email alerts
|

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In addition to changes in litter quality, interspecific root interactions may also affect the relative species abundances in mixed communities. Such changes in species relative abundance, particularly proportions of different growth forms with contrasting litter properties and decomposability, may be one of the main drivers of changes in litter decomposition along species richness gradients (Chen et al, 2017 ; Wang et al, 2022 ). However, we found that the decomposition of artificial root litter mixtures of known composition was still significantly slower than expected based on the decomposition rates of component litters in monoculture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in litter quality, interspecific root interactions may also affect the relative species abundances in mixed communities. Such changes in species relative abundance, particularly proportions of different growth forms with contrasting litter properties and decomposability, may be one of the main drivers of changes in litter decomposition along species richness gradients (Chen et al, 2017 ; Wang et al, 2022 ). However, we found that the decomposition of artificial root litter mixtures of known composition was still significantly slower than expected based on the decomposition rates of component litters in monoculture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of the soil at which the litter is deposited can also have a substantial impact on the consequences of litter decomposition from an invasive plant on native species and soils (Sun et al, 2022b). However, an exception is cases of severe droughts, where increasing species richness has been shown to slow the rate of litter decomposition (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of species diversity, nitrogen-dependent litter decomposition is always present in plant communities (Pereira et al, 2021;Wang et al, 2022). Some species have faster decomposition rates and nutrient release than others.…”
Section: Introductionmentioning
confidence: 99%